2015
DOI: 10.1038/srep14591
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Corrigendum: Epigenetic regulation of the nuclear-coded GCAT and SHMT2 genes confers human age-associated mitochondrial respiration defects

Abstract: Age-associated accumulation of somatic mutations in mitochondrial DNA (mtDNA) has been proposed to be responsible for the age-associated mitochondrial respiration defects found in elderly human subjects. We carried out reprogramming of human fibroblast lines derived from elderly subjects by generating their induced pluripotent stem cells (iPSCs), and examined another possibility, namely that these aging phenotypes are controlled not by mutations but by epigenetic regulation. Here, we show that reprogramming of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Arginine and proline metabolism contains several metabolic pathways we mentioned in the AD-related pathways, such glutathione, glycine, and polyamine metabolism. Evidence has shown that these pathways are related to aging ( Minois et al, 2011 ; Hashizume et al, 2015 ; Weschawalit et al, 2017 ). We can see that arginine and proline metabolism has been shown to play a role in prospective studies of the progression from no disease to MCI and eventually AD; likewise, arginine and proline metabolism appears in the pathways related to natural aging.…”
Section: Discussionmentioning
confidence: 99%
“…Arginine and proline metabolism contains several metabolic pathways we mentioned in the AD-related pathways, such glutathione, glycine, and polyamine metabolism. Evidence has shown that these pathways are related to aging ( Minois et al, 2011 ; Hashizume et al, 2015 ; Weschawalit et al, 2017 ). We can see that arginine and proline metabolism has been shown to play a role in prospective studies of the progression from no disease to MCI and eventually AD; likewise, arginine and proline metabolism appears in the pathways related to natural aging.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse LOTUS (mLOTUS) cDNA and the Venus fluorescent protein ( Nagai et al., 2002 ; Duran-Avelar et al., 2018 ) gene connected by an internal ribosomal entry site (IRES) were cloned into the lentiviral vector CSII-EF1α, yielding pCSII-EF1α-mLOTUS-IRES-Venus ( Figure 1 A) ( Iida et al., 2017 ). Recombinant lentiviral vector production and titer determination were performed as described previously ( Hashizume et al., 2015 ).…”
Section: Methodsmentioning
confidence: 99%